AKTIVITAS ANTIJAMUR, ANTIBAKTERI DAN PENYEMBUHAN LUKA EKSTRAK RESIN JERNANG - Totok Kartono Waluyo; Gunawan Pasaribu (Jurnal Penelitian Hasil Hutan, 2015)
“Jernang” or known as dragon’s blood is one of high value non-wood forest products originated from Indonesian forest. Dragon’s blood which is a red colored resin secreted from rattan’s fruits has been utilised traditionally. This paper determines the antibacterial and antifungal capability againts bacteria (Basilus subtilis and Staphylococcus aureus) and fungus (Candida albicans and Aspergillus flavus). The antibacterial and antifungal capability was determined based on the in vivo wound healing test on rabbit. The result shows that in general, “jernang” provides antibacterial and antifungal capacity against bacteria and fungus. The ethyl acetate jernang extract which were effective as antimicrobial to heal the wound.